The Impact of the Implementation of Financial Accounting Standards on the Quality of Financial Reports in Small and Medium Enterprises (SMEs) in Indonesia - Wahyuni Istiqomah Adha; Mulyati Akib (PT. Banjarese Pacific Indonesia, 2025)
This study aims to analyze the effect of the application of Financial Accounting Standards (FAS) on the quality of financial statements in Small and Medium Enterprises (SMEs) in Indonesia. Quality financial reports are very important for SMEs, because they serve as a transparent communication tool between management and stakeholders, as well as a basis for making informed decisions. SMEs have a significant contribution to the Indonesian economy, contributing around 60% of gross domestic product (GDP) and absorbing more than 97% of the workforce. However, many SMEs still face challenges in preparing financial statements in accordance with accounting standards. This study uses a systematic literature review method to collect and analyze various relevant studies on the application of SAK and its impact on the quality of financial statements. The results showed that the application of SAK significantly improved the transparency, relevance, and reliability of SMEs' financial statements. In addition, the study also identified various factors that influence the adoption of SAK, such as the education level of business owners, access to accounting training, and support from the government. The conclusion of this study confirms the importance of good accounting standards implementation to improve the quality of SMEs' financial statements, which in turn can improve the competitiveness and performance of businesses in the market. Recommendations are given to improve the understanding and application of SAK among SMEs in Indonesia.